The Influence of Service Quality and Social Media Marketing on Consumer Satisfaction - Haryanti, Nik; Sa'diyah, Dewi Fitrotus; Winarto, Winarto; Supriyono, Supriyono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this study was to determine the effect of service quality and social media marketing on customer satisfaction at PT Putra Rinjani Blitar. The sample in this research is 100 consumer employees.With the sampling technique using purposive sampling, namely the technique of determining the sample with certain considerations. Data analysis using multiple regression test. The results of his research show thatthere is an influence of service quality on customer satisfaction, there is an influence of social media marketing on customer satisfaction and there is an influence of service quality and social media marketing on customer satisfaction.